ARCHITECTURAL HERITAGE: CONTRIBUTION TO THE CITY BRAND STRATEGY - Popescu, Gabriela Virginia (Ecoforum Journal, 2021)
Our paper aims at highlighting the way two very different defining elements (concrete, buildings, vehicle traffic, urban landscape and music, lifestyle, feelings etc.) of a place melting together provide a contribution to a very early city branding strategy. We focus on the case of Bucharest between the two World Wars. It is the period when its architecture dramatically changed in accordance to the newest and daring construction techniques and technologies, design trends and people preoccupations for wellbeing. This heritage is creatively translated into musical compositions that enriched the Bucharest lifestyle of that period and, partially, travelled the time up to nowadays. The research is based on the content analyses of musical compositions and performances of the famous artists in the period between 1920 - 1940. As conclusion, the research reveals a dynamic and friendly city and a vibrant urban life, making the interwar Bucharest as a liveable city, as it should be characterised in the theory and practice of the place brand. This way, the slow the process of losing authenticity and to anonymizing of any place (city, region) is going through at a certain period of time, with more or less cyclicity. <!–[endif]–>